Analisis Potensi Daya Tarik Wisata di Desa Wisata Rintisan Cilengkrang, Kabupaten Bandung - Annisa Lazuardina; Eldo Delamontano; Zendra Haris Prasetya; Taqiy Gusdi Baitulloh; Evi Novianti (JURNAL AKADEMISI VOKASI, 2024)
This study aims to identify and analyze the tourism attraction potential of Cilengkrang Tourism Village in Bandung Regency. The village possesses diverse tourism potentials, including natural beauty, cultural richness, and man-made attractions such as bamboo crafts and coffee products. The research employs observation, in-depth interviews, and SWOT matrix analysis to evaluate tourism potentials and formulate development strategies. The findings reveal that cultural potential, such as Benjang Art, holds the highest development priority, followed by natural attractions like Cilengkrang Waterfall and Padaemut Hill, as well as man-made products like Manglayang Coffee SMEs. Recommended strategies include improving accessibility, providing technology training for locals, establishing community-based tourism organizations, and strengthening disaster mitigation efforts. The implications indicate that local community involvement, particularly among youth, and support from local governments are crucial for sustainable tourism management. This study provides new insights into tourism village development based on local potential, while opening opportunities for further research on the economic, social, and environmental impacts of tourism management.